2016
DOI: 10.3823/790
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Bacterial Peritonitis in the Medical Intensive Care Unit of a University Hospital in Egypt: Frequency, Bacteriological Profile, Risk Factors and Outcomes

Abstract: Objective: To assess the frequency of spontaneous bacterial peritonitis (SBP) in the Medical intensive care unit (ICU) of Zagazig University Hospital, identify the causative organisms, their susceptibility to antimicrobials, and to determine risk factors and clinical outcomes. Methods:One hundred and eighty-nine ascitic patients suffered of liver cirrhosis were included in this prospective study. Medical history, physical examination, radiological reports and assessment of disease severity were done. Diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
1
0
1
Order By: Relevance
“…The prevalence of SBP in this study was nearly similar to that reported by different local studies in Egypt as it was 57% in Kasr Alaini [27], 50% [28] and 76.7% [29] by two different studies in Mansoura, 56.1% in Zagazig [24] and 62% in Aswan [30]. While other Egyptian studies reported a lower prevalence of SBP as it was 13% in Al-Hussein University hospital [31], 31% in Sohag [32], 44.3% in Assuit [33], 31% in Ain Shams [34], 19.6% in Menoufia [35],…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of SBP in this study was nearly similar to that reported by different local studies in Egypt as it was 57% in Kasr Alaini [27], 50% [28] and 76.7% [29] by two different studies in Mansoura, 56.1% in Zagazig [24] and 62% in Aswan [30]. While other Egyptian studies reported a lower prevalence of SBP as it was 13% in Al-Hussein University hospital [31], 31% in Sohag [32], 44.3% in Assuit [33], 31% in Ain Shams [34], 19.6% in Menoufia [35],…”
Section: Discussionsupporting
confidence: 88%
“…This agreed with Suvak et al, and Liu et al, who found that ESR is less sensitive and accurate as an acute-phase reactant than the C reactive protein. This result was in disagreement with Yousef et al [12][13][14].…”
Section: Discussioncontrasting
confidence: 71%